2013
DOI: 10.1002/pits.21726
|View full text |Cite
|
Sign up to set email alerts
|

Social Comparison in Physical Education: An Examination of the Relationship Between Two Frames of Reference and Engagement, Disaffection, and Physical Self-Concept

Abstract: Drawing from theory and research into social comparison processes, the present study sought to determine children's motives for comparison in addition to the coexistence of class and individual comparisons in school physical education. The main and interactive effects of these types of comparisons were examined in relation to pupils’ physical self‐concept, as well as self‐reported behavioral engagement and disaffection in class. In total, 545 children (Mage = 13.89 years, SD = 1.57 years) from two schools in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example: ‘When you think you’re doing something good like and you look at Chloe and she’s doing it perfect and she’s getting the praise’ (girl, below average ability); ‘Yeah, when like we have like a set sort of drill in class I like stand out compared to the others, it’s really easy’ (boy, above average ability). Barnes and Spray (2013) suggest that PE lessons are rife with social comparison information. Within the current study, this social comparison promoted positive and negative feelings about students’ PE competence depending upon their self-perceptions of ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example: ‘When you think you’re doing something good like and you look at Chloe and she’s doing it perfect and she’s getting the praise’ (girl, below average ability); ‘Yeah, when like we have like a set sort of drill in class I like stand out compared to the others, it’s really easy’ (boy, above average ability). Barnes and Spray (2013) suggest that PE lessons are rife with social comparison information. Within the current study, this social comparison promoted positive and negative feelings about students’ PE competence depending upon their self-perceptions of ability.…”
Section: Discussionmentioning
confidence: 99%
“…Within the current study, this social comparison promoted positive and negative feelings about students’ PE competence depending upon their self-perceptions of ability. It has been proposed that some children are motivated to compare by the desire to self-improve, evaluate and enhance, whereas others are not because they may be disaffected and disengaged (Barnes and Spray, 2013; Butler, 1992; Lubbers et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To negate the undesirable impact of upward social comparisons to more able peers the use of homogenous ability groups are suggested. This recommendation extends the suggestion by Barnes and Spray [36], to encourage similar ability comparison in physical education classes, into a physiology research context. Body dissatisfaction concerns, in particular when exercising in front of boys, can be detrimental to adolescent girls participation in physical activity [27,35].…”
Section: Discussionmentioning
confidence: 86%
“…A number of researchers reported that the need of adolescents to be close to friends and to create new friends was found to be a main motive for participating in the lessons (e.g., Bryan & Solmon, 2012;Rosenkranz et al, 2012;Rubin & Raviv, 1999). Physical education teachers can influence and direct meaningful social processes, such as fostering proper means of communication, demonstrating caring and concern for others, developing relationships based on enjoyment and a feeling of belonging to a group, developing leadership, accepting and containing the other, accepting oneself as part of self-identity development, encouraging independence, fostering creativity, and others (see Barnes & Spray, 2013;Grimminger, 2013;Sansock, 2007, Wallhead, Garn, & Vidoni, 2013.…”
Section: Introductionmentioning
confidence: 99%